A infância e sua escolarização nas páginas dos jornais cuiabanos (1910-1930) - Silva, Marijâne Silveira da (2015)
This thesis aims to analyze some childhood education representations materialized in newspapers from Cuiabá, through the game of scales (REVEL, 1998) and the articulation of local and global. The objective was to examine how primary school was portrayed by Cuiabá’s press, trying to realize how newspapers of different political and ideological matrices discussed the issues related to primary education, and contribute to the expansion of knowledge about the history of education in Mato Grosso. The time frame has as landmarks two reforms regulated in the period, and that caused significant changes in primary education of the state: the first by Decree No. 265, dated October 22, 1910, and the other established by Decree No. 759, of April 22, 1927. The research was directed by the following questions: how was primary school portrayed by Cuiabá’s press during the first three decades of the twentieth century? What were the childhood/child representations stamped in Cuiabá’s press? The research methodology, of historical approach, prioritized the location, survey, gathering, selection and analysis of documentary sources, relevant to the research subject and to the context in which it stood. For the analysis, it was elected childhood and its education from the perspective of Cuiabá’s newspapers as a guide. I emphasize, however, that the research does not constitute in a history of the press, but sought to contribute to writing a history of primary education. The articles printed on the newspapers were articulated with a wide range of sources such as legislation, reports, messages, minutes books, etc. On the privileged period, the journalistic production of some journals was born and disappeared swiftly, reaching over a hundred newspapers running across the state. The press is seen, then, as an important space for the circulation of ideas and affirmation of positions. The survey of papers published in the period concerned was held in the collections of the capital of Mato Grosso - Cuiabá, together with the Public Archives of Mato Grosso (APMT), the Barão de Melgaço House (CBM), the Regional Historical Documentation and Information Center of the Federal University of Mato Grosso (NDIHR / UFMT), and online assets from the Digital Newspaper Library of the National Library (RJ). The analysis of the documents was based on texts of Roger Chartier (1990; 2002) rich in subsidies about the concept of representations, anchored on the assumptions of Cultural History. From the systematic inventory of news, information and articles published in newspapers of Cuiabá, it was found that the educational discourses were presented in different formats, namely, chronicles, poems, advertisements, articles, among others. It is possible to see on the pages of printed newspapers the record of what happened daily. In relating the events, the printed newspaper hinted the image people had of children and their education, as well as the ideas that permeated the period. As a social educator, the newspapers that circulated in society at that time got its readers to form concepts about the role of the teacher, of school, of children and of students. Reconstruct or (re) write the history of Mato Grosso’s primary education from the perspective of Cuiabá’s newspapers allowed to reveal aspects of society that were not identified in the official written sources, so the newspaper's use is considered an important historical source that contributes to the enrichment of studies about the history of regional education and, perhaps, national.